ANALISIS PENGARUH KEWIRAUSAHAAN, MODAL SOSIAL, DAN INOVASI TERHADAP KINERJA USAHA MIKRO DI ERA EKONOMI DIGITAL" (STUDI KASUS MAHASISWA STIE-TN DUMAI) - Suprapto, Bambang; Chintia Sari, Cinta; Widya Rahman, Rani (Jurnal Daya Saing, 2025)
This study aims to examine the effect of entrepreneurship, social capital, and innovation on the performance of micro-enterprises run by students of STIE-TN Dumai in the digital economy era. Using a quantitative approach with a survey method, data were collected from 95 student respondents who own micro-enterprises. The analysis was conducted using multiple linear regression via SPSS version 20.0. The results show that entrepreneurship and social capital have a positive and significant effect on business performance. Surprisingly, innovation has a negative and significant effect. Simultaneously, all three variables significantly affect micro-business performance, explaining 39.4% of the variance. This finding implies that while entrepreneurship and social capital strengthen student-led businesses, innovation may negatively impact performance if not aligned with market needs or lacking in managerial readiness. Future research is expected to explore other influencing factors, such as digital literacy, access to capital, and institutional support, to strengthen the sustainability of student micro-enterprises in the digital era